2023
DOI: 10.1177/17562848231155022
|View full text |Cite
|
Sign up to set email alerts
|

Effect of antidepressants on psychological comorbidities, disease activity, and quality of life in inflammatory bowel disease: a systematic review and meta-analysis

Abstract: Background: Patients with inflammatory bowel disease (IBD) are often accompanied by a more significant burden of depression or anxiety, and approximately one-third are prescribed antidepressants. However, previous studies on the efficacy of antidepressants in IBD have shown inconsistent results. Objectives: To evaluate the effect of antidepressants on depression, anxiety, disease activity, and quality of life (QoL) in IBD patients. Design: A systematic review and meta-analysis. Methods: We searched MEDLINE via… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 56 publications
(73 reference statements)
0
3
0
Order By: Relevance
“…Based on these descriptive data, we identified the largest systematic reviews within each medical disease. Data on primary and secondary outcome measures for these 73 systematic reviews are presented in eTable 7 in Supplement 2 for treatment of depression and in eTable 8 in Supplement 2 for prevention of depression.…”
Section: Resultsmentioning
confidence: 99%
“…Based on these descriptive data, we identified the largest systematic reviews within each medical disease. Data on primary and secondary outcome measures for these 73 systematic reviews are presented in eTable 7 in Supplement 2 for treatment of depression and in eTable 8 in Supplement 2 for prevention of depression.…”
Section: Resultsmentioning
confidence: 99%
“…For example, patients with IBD frequently have active gastrointestinal symptoms, chronic pain, elevated systemic inflammation and can have impaired intestinal absorption [ 5 ], emphasising the need for clinical trials of antidepressants specifically in IBD. Whilst a recent meta-analysis found benefit of antidepressants for depression in IBD, its findings were primarily based on studies with a high risk of bias [ 7 ]. Our findings, therefore, advance the literature by showing that antidepressants are more effective in IBD when meta-analysing based on RCTs.…”
Section: Discussionmentioning
confidence: 99%
“…A recent meta-analysis found antidepressants to be effective in patients with IBD. The findings of this synthesis, however, were based primarily on studies where randomisation or blinding procedures were not reported [ 7 ], thereby seriously undermining the validity of the findings. Furthermore, the authors did not analyse by antidepressant class, meaning it remains unclear which specific antidepressants are likely to be most beneficial in patients with IBD.…”
Section: Introductionmentioning
confidence: 99%